Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Solve the following equation for [tex]B[/tex]:

[tex]7B = -g^3 B + h[/tex]


Sagot :

Sure, let's solve the equation [tex]\( 7B = -g^3 B + h \)[/tex] for [tex]\( B \)[/tex].

Step-by-Step Solution:

1. Start with the given equation:
[tex]\[ 7B = -g^3 B + h \][/tex]

2. Move all terms involving [tex]\( B \)[/tex] to one side of the equation. This helps in isolating [tex]\( B \)[/tex]:
[tex]\[ 7B + g^3 B = h \][/tex]

3. Factor out [tex]\( B \)[/tex] from the left-hand side:
[tex]\[ B(7 + g^3) = h \][/tex]

4. To solve for [tex]\( B \)[/tex], divide both sides of the equation by [tex]\( 7 + g^3 \)[/tex]:
[tex]\[ B = \frac{h}{7 + g^3} \][/tex]

So the solution to the equation [tex]\( 7B = -g^3 B + h \)[/tex] is:
[tex]\[ B = \frac{h}{7 + g^3} \][/tex]